Технічні науки в загальній системі наук - Гріффен, Л.О. (Питання історії науки і техніки, 2007)
Исследование положения технических наук в общей системе наук об объективной реальности показывает, что технические науки являются полноправной составной частью этой системы. Однако они имеют собственный предмет и особые методы, особенность которых обусловлена как природно-антропогенной спецификой предмета, так и их креативным общественным назначением. The research of a situation of engineering science in general system of sciences about the objective reality shows, that the engineering science is a full component of this system. However they have an own subject and special methods, which feature is caused as natural-anthropogenic specificity of a subject, and them creative by social purpose.